KONSEP PENDIDIKAN AKHLAK DALAM AL-QURAN (ANALISIS TAFSIR SURAT AL-BAQARAH AYAT 186) - Ngatiran, Ngatiran (Jurnal Pendidikan Guru, 2017)
The success of oral education is need for a serious and cooperation of all stakeholders, from educational institutions (principals and all components), parents, community, and goverment and central goverment), all do what is best for education, either moral or spiritual. The concept of character education or moral education can be viewed from the standpoint of surah Al-Baqoroh pargraph 186. This paper focuses the discussion on the interpretation taâdib the words of rasyada-yarsyudu-rusyda (can be manual, straight and well, dodgy) or arsyada-yursyidu-irsyaada (showed the right path) in surah Al-Baqoroh paragraph 186, as well as its implementation in contemporary Islamic education.